2017
DOI: 10.1039/c6ra27452h
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Na2O on the fast diffusion layer around diopside crystals

Abstract: The Na+ content in the glass phase is higher than that in the crystal phase, which leads to the establishment of a fast diffusion layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…According to accepted procedures, energy-dispersive spectroscopy (EDS) is helpful for this task. For example, Fan et al 11 reported the sodium content increase around a diopside crystal in a nonstoichiometric glass-ceramic detected by EDS in a line-scanning mode. Zones enriched in calcium around lithium metasilicate crystals in an Li 2 O⋅CaO⋅SiO 2 glass 4 and in barium around lithium disilicate crystals in an Li 2 O⋅BaO⋅SiO 2 glass 5 were also revealed by scanning electron microscopy (SEM) with backscattered electrons (BSEs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to accepted procedures, energy-dispersive spectroscopy (EDS) is helpful for this task. For example, Fan et al 11 reported the sodium content increase around a diopside crystal in a nonstoichiometric glass-ceramic detected by EDS in a line-scanning mode. Zones enriched in calcium around lithium metasilicate crystals in an Li 2 O⋅CaO⋅SiO 2 glass 4 and in barium around lithium disilicate crystals in an Li 2 O⋅BaO⋅SiO 2 glass 5 were also revealed by scanning electron microscopy (SEM) with backscattered electrons (BSEs).…”
Section: Introductionmentioning
confidence: 99%
“…According to accepted procedures, energy‐dispersive spectroscopy (EDS) is helpful for this task. For example, Fan et al 11 . reported the sodium content increase around a diopside crystal in a nonstoichiometric glass–ceramic detected by EDS in a line‐scanning mode.…”
Section: Introductionmentioning
confidence: 99%